2000
DOI: 10.1164/ajrccm.162.2.9912058
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Declines in Pulmonary Function Following Pneumonia in Human Immunodeficiency Virus-Infected Persons

Abstract: Human immunodeficiency virus (HIV)-associated respiratory infections, most notably Pneumocystis carinii pneumonia (PCP), but also bacterial pneumonia (BP), result in reductions in lung function that have been studied mainly during the course of acute infection. Whether HIV-associated pneumonias also cause permanent changes in pulmonary function is unknown. In this study we investigated the long-term effects of PCP and BP on pulmonary function in a cohort of HIV-infected persons. One thousand, one hundred forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 21 publications
3
111
0
5
Order By: Relevance
“…DL CO , FEV 1 , and peak flow decrease during acute PCP and for at least 3 months after infection (7,21). These changes may be permanent because PCP leads to accelerated declines in FEV 1 , FEV 1 /FVC, and DL CO beyond that expected from age and smoking history (22). We have recently shown that Pccolonized HIV-infected outpatients have worse airway obstruction than Pc-negative HIV-infected persons, independent of smoking history (23).…”
Section: Infectionsmentioning
confidence: 97%
“…DL CO , FEV 1 , and peak flow decrease during acute PCP and for at least 3 months after infection (7,21). These changes may be permanent because PCP leads to accelerated declines in FEV 1 , FEV 1 /FVC, and DL CO beyond that expected from age and smoking history (22). We have recently shown that Pccolonized HIV-infected outpatients have worse airway obstruction than Pc-negative HIV-infected persons, independent of smoking history (23).…”
Section: Infectionsmentioning
confidence: 97%
“…Importantly, both bacterial pneumonia and PCP have been found to be associated with a decline in lung function (as measured by FEV 1 , FVC, FEV 1 /FVC ratio and diffusing capacity of carbon monoxide) that persists following infection [81]. This highlights the importance of the prevention of opportunistic infections in HIV-infected persons.…”
Section: Mortalitymentioning
confidence: 99%
“…These numbers give an idea of the magnitude of the problem of pulmonary infections in HIV patients. Moreover, it has been suggested that Pneumocystis pneumonia (PCP), tuberculosis (TB) and bacterial pneumonia are associated with a significantly worse subsequent HIV disease course, even a permanent decline in pulmonary function [16][17][18][19], although not all studies agree with these findings [20].…”
mentioning
confidence: 99%